Hox genes and regional patterning of the vertebrate body plan - Mallo, Moises (2016)
Several decades have passed since the discovery of Hox genes in the fruit fly Drosophila melanogaster. Their unique ability to regulate morphologies along the anteroposterior (AP) axis (Lewis, 1978) earned them well-deserved attention as important regulators of embryonic development. Phenotypes due to loss- and gain-of-function mutations in mouse Hox genes have revealed that the spatio-temporally controlled expression of these genes is critical for the correct morphogenesis of embryonic axial structures. Here, we review recent novel insight into the modalities of Hox protein function in imparting specific identity to anatomical regions of the vertebral column, and in controlling the emergence of these tissues concomitantly with providing them with axial identity. The control of these functions must have been intimately linked to the shaping of the body plan during evolution.